Treatment options for patients with CADASIL and large-scale cerebral infarction: mechanical thrombectomy and antiplatelet therapy—A case report - Xiao, Shuyue; Ke, Man; Cai, Kaiwei; Xu, Anding; Chen, Menglong (Frontiers in Neurology, 2024)
Background: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is an autosomal dominant inherited arterial disease, with lacunar infarction resulting from intracranial small vessel lesions being the most prevalent clinical manifestation of CADASIL. However, large-scale cerebral infarction caused by intracranial non-small vessels occlusion is relatively uncommon, and reports of vascular intervention and long-term antiplatelet drug treatment for patients with CADASIL and large-scale cerebral infarction are rarer.We reported a 52-year-old male who experienced a significant cerebral infarction due to an occlusion in the second segment of the left middle cerebral artery, four months subsequent to being diagnosed with CADASIL. Following the benefit and risk assessment, the patient underwent intracranial vascular thrombectomy and balloon dilation angioplasty. Subsequently, he was administered dual antiplatelet therapy for three months, followed by mono antiplatelet therapy.Results: After undergoing intracranial vascular intervention and receiving antiplatelet therapy, significant improvement in the symptoms were observed. The National Institutes of Health Stroke Scale score decreased from 6 to 2 points, and no bleeding lesions were detected on the head computed tomography during regular follow-up visits after discharge.Our case highlights the possibility that patients with CADASIL may also encounter extensive cerebral infarction resulting from stenosis or occlusion of intracranial non-small vessels.Considering the specific circumstances of the patient, intravascular intervention and antiplatelet therapy can be regarded as viable treatment options for individuals with CADASIL.